2015
DOI: 10.1177/1359105315573441
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences and correlates of extreme dieting behaviours in US adolescents

Abstract: This paper examined correlates of and gender differences in extreme dieting behaviours (EDBs) among 15,425 US adolescents from the 2011 Youth Risk Behavior Survey. Suicidal thoughts and plans, and binge drinking were related to EDBs in females, but not in males.Suicide attempts, daily smoking, and marijuana use were related to EDBs in males, but not females. Results suggest EDBs are associated with a range of negative psychosocial factors and substance use behaviours, and that these differ for boys and girls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…This paradox was also seen in our study results. The proportion of female and male patients in this study is 3.7:1, which is similar to the domestic literature, perhaps because in China women are more affected by negative life events, eventually producing the impulse to commit suicide [ 16 , 17 ]. Moreover, it was reported that 62% of women who committed suicide had made previous suicide attempts, and 62% of men who committed suicide had not previously made such an attempt [ 18 ]; therefore, women are more likely to attempt suicide while men are more likely to die from suicide [ 14 , 19 ].…”
Section: Discussionsupporting
confidence: 83%
“…This paradox was also seen in our study results. The proportion of female and male patients in this study is 3.7:1, which is similar to the domestic literature, perhaps because in China women are more affected by negative life events, eventually producing the impulse to commit suicide [ 16 , 17 ]. Moreover, it was reported that 62% of women who committed suicide had made previous suicide attempts, and 62% of men who committed suicide had not previously made such an attempt [ 18 ]; therefore, women are more likely to attempt suicide while men are more likely to die from suicide [ 14 , 19 ].…”
Section: Discussionsupporting
confidence: 83%
“…The average result of health-related behaviour obtained in the study group (M = 72.4, SD = 11.4) highlighted the average level of the variable. Significant, though small, differences in the overall rate of health-related behaviour were noted between boys and girls, an observation which has been confirmed by other studies [31].…”
Section: Discussionsupporting
confidence: 83%
“…Muscularity-oriented disordered eating is less likely to be detected and treated in clinical practice , and may result in marked medical instability (Murray, Accurso, Griffiths, & Nagata, 2017). For instance, extreme dieting in male populations is associated with suicide attempts, daily smoking and marijuana use (Brown, Kola-Palmer, & Dhingra, 2015). Our findings indicate that addressing muscularity concerns may reduce distress associated with body disturbance, as well as mitigate risk for depressive distress, binge drinking, dieting and use of muscle-building products.…”
Section: Discussionmentioning
confidence: 80%